The house and the city. Adaptable residential architectures: City and housing facing the contemporary challenge (ARQUISUR Revista, 2022)
The contemporary demands on the living conditions (in all the spatial categories that the activity implies from the intimate to the public) suggest a glance at the houses as the ba-sic unit of production of the urban residential fabric, and the block as one of the charac-teristic forms of it. In this sense, it is interesting to investigate the possibilities of the urban block production within the regular fabric of intermediate-scale cities. The latter assumes the logic of construction by private initiative lot by lot, promoting conditions that lead to coherent results, both from the resultant urban space as the form that contains it. From project research, an approach to the subject starts from its theoretical aspects, simultane-ously with verifications in project explorations applied to case studies. The main aspects are the typological development of collective housing units in the lot, the block ́s program-matic stratification, and the study of its progressive replacement over time. The results show the spatial and formal possibilities and the limitations of the current modes of production, implying a necessary look at architectural, technical, or regulatory aspects on which it also requires to intervene.
Keywords: housing; adaptability; block; fabric; city